The saint who stole my heart ebook A regency rogues novel. - Sloane, Stefanie (Regency Rogues, 2012)
Desire, danger, intrigue, and steamy seduction unite a sexy spymaster and an intrepid bluestocking as Stefanie Sloane's luscious new series continues. Possessed of a brilliant mind and a love for puzzles, Dashiell Matthews, Viscount Carrington, is a crucial member of the elite Young Corinthians spy league. Assuming the façade of an addle-brained Adonis, he hunts for a notorious London murderer known as the Rook. When fate causes him to cross paths with Miss Elena Barnes, Dash discovers an enigma that will prove delightfully intoxicating to unravel: a voluptuous beauty as intelligent as she is fearless. Only the lure of a collection of rare books bequeathed to her family by Dash's late father could tempt Elena from her cozy rural life to the crush and vanity of London. But if Elena finds his lordship to be the most impossibly beautiful man she's ever seen, he also seems to be the stupidest. Which made her body's shameless response to his masterful seduction all the more unfathomable. Yet when she discovers Dash's mission to track the dangerous Rook, she willingly risks everything--her trust, her heart, her very life--to join him. From the Paperback edition.